INFLUENCE OF INTERNATIONALIZATION PROCESSES IN THE HIGHER EDUCATION INSTITUTION ON THE DEVELOPMENT OF INTERCULTURAL COMPETENCE - Virgailaitė-Mečkauskaitė, Eglė; Lubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Since integration and globalization processes are accelerating in the world, the demand to internationalize education and studies increases as well as parameters of the activities of higher education institutions change. International competitive ability of European higher education area, international mobility and high level of university graduates’ employment as well as successful integration into international labour market are the main aims of Bologna process. Bologna declaration, various documents of conventions (European convention of higher education institutions, Salamanca) and communiqué documents (of Prague; Berlin; Bergen) related to the declaration devoted to the creation of common European Higher Education Area raise the necessity of higher education policy emphasizing internationalization, the conception of lifelong learning. The documents mentioned above emphasize the development of European dimensions and content internationalization in study programmes, training of a flexible, mobile, constantly improving and public active specialist who will integrate into the competitive labour market, mobility of the academic community and international cooperation. The development of intercultural competence becomes a more topical subject of the research taking globalization processes into consideration. That is why it is important to understand the influence of internationalization processes in the institution on the development of Master’s degree (MA) students’ intercultural competence through their experience gained in the study process. The aim of the research presented in this article is to discuss the influence of internationalization processes in the institution on the development of MA students’ intercultural competence. A scientific problem question raised in the research is how MA students telling their life story reveal the experience gained in the process of higher education internationalization which influenced the development of their intercultural competence.